Distribution of earth pressure behind retaining walls considering different approaches - Salman, F.A.; Al-Shakarchi, Y.J.; Husain, H.M.; Sabre, D.K. (Academic Journals, 2010)
In this paper, the earth pressure distribution generated behind a retaining wall is estimated by the finite element method and compared with that obtained from classical earth pressure theories. In this analysis, the behavior of the soil is assumed to be elasto-plastic with Mohr-Coulomb failure criterion. The concrete retaining wall is represented by linear elastic model. The thin layer interface element proposed by Desai et al. (1984) is used to represent the interface between the wall and the surrounding soil. A two-dimensional plane-strain finite element computer program CRISP is utilized after some modification. The results show that the distribution of earth pressure depends on the mode of wall movement (whether translation, rotation or both), and the active earth pressure obtained from the finite element analysis is close to Coulomb's solution in case of bottom wall rotation. Whereas, in case of top wall rotation, the obtained earth pressure is greater than that of Coulomb solution. This is mainly because Coulomb equation is originally based on wall rotating about its base (failure mechanism).